Dual normalization of the tangentially degenerate surface - Гребенюк, М. Ф. (Proceedings of National Aviation University (archive), 2002)
The differential geometry of tangentially degenerate surfaces of non-Euclidean space is considered. Differential equations are obtained that determine the tangentially degenerate surface in space (referred to a moving autopollar normalized frame, dual normalization of the guide surface in the sense of AP Norden